Softening behaviour of alumina reinforced copper processed by equal channel angular pressing. (February 2014) - Ranjbar Motlagh, S.; Maghsoudi, M. H.; Serajzadeh, S.
<x content-type="archive" xml:space="preserve">Abstract</x> In this present work, the softening behaviour of Cu–1·1 wt-%Al2O3 alloy containing nanometric alumina particles was investigated. Single pass equal channel angular pressing was first applied on cylindrical specimens, and then, the deformed samples were subjected to annealing treatments in the temperature range of 700–1000°C. Afterwards, finite element analysis, microstructural observations, Vickers hardness and shear punch testing were employed to study strain distribution as well as the recrystallisation behaviour of the examined alloy. It was found that the alloy is softened at 800°C or above, which shows its high thermal stability. Furthermore, a very fine completely recrystallised microstructure was obtained via a continuous mechanism of recrystallisation at 1000°C. The activation energy of recrystallisation was measured to be ∼181 kJ mol−1, which offers a high thermal stability in high temperature applications of this alloy.